Critical Pragmatic Model of Analysis: Americanism Ideolgy as an Example - Al-Hindawi, Fareed Hameed (International Journal of Psychosocial Rehabilitation, 2019)
Ideologized language is a fact that shapes the way we live and use language as producers and receivers, but there have always been the beliefs and value systems of those who hold power and dominance. The intention of those power holders is to represent and convey their value system and beliefs to others for the purpose of influencing and convincing them to adopt or advocate this ideology. We have been long exposed to the idea that America is a unique country, it is the most powerful country at all aspects. Moreover, we have long been convinced that the American life style is ideal and for that, the concept of American dream is formulated. Whether fact or myth, those ideas represent an integral part of the American social and political thinking and Americans are trying through different means including, Hollywood film industry, to reinforce these ideas. Thus, this issue has critical significance, it can be investigated from the perspective of critical studies, particularly, critical pragmatics. Accordingly, the present study confine itself to developing a critical pragmatic model of analysis that can be used in analyzing Americanism ideology or any social practice of power or social struggle nature. This can be achieved through the integration of pragmatic aspects with concepts of critical studies. However, the present study attempts to answer this question: What are the common pragmatic aspects used in representing Americanism ideology? It, then, aims to develop an analytical apparatus for critical pragmatics in revealing ideologized utterance through pragmatic strategies. The study is qualitative and is confined to analysis of selected extracts form three Hollywood films. The data analysis has proved the workability of the model of analysis developed in this study and that certain pragmatic aspects are utilized to reveal this issue of a critical nature.